2021
DOI: 10.1016/j.est.2021.102641
|View full text |Cite
|
Sign up to set email alerts
|

Techno-economic optimisation of battery storage for grid-level energy services using curtailed energy from wind

Abstract: The increasing integration of renewable energy sources makes balancing a grid challenging due to their intermittency. Renewable energy can be curtailed especially when production exceeds demand or when there is transmission and/or distribution network congestions within a grid. However, curtailment would become unnecessary with battery storage, provided the battery storage has enough available storage capacity, which can store energy during the time of excess generation and discharge it to the grid once the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 40 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…An example of this would be the work of the authors of Ref. [33], who replaced diesel generators in a university campus microgrid with an unreliable grid power supply with a PV-BESS hybrid system that reduced peak-hour energy purchases from the grid significantly by phasing out diesel generators almost entirely. The authors also concluded that the transition to a PV-BESS hybrid system yielded substantial annual savings and calculated the payback period to be around 6 years.…”
Section: Environmental Impactmentioning
confidence: 99%
“…An example of this would be the work of the authors of Ref. [33], who replaced diesel generators in a university campus microgrid with an unreliable grid power supply with a PV-BESS hybrid system that reduced peak-hour energy purchases from the grid significantly by phasing out diesel generators almost entirely. The authors also concluded that the transition to a PV-BESS hybrid system yielded substantial annual savings and calculated the payback period to be around 6 years.…”
Section: Environmental Impactmentioning
confidence: 99%
“…It is proposed to integrate BESSs with other theologies, such as dynamic thermal rating systems, to manage wind power intermittency to alleviate congestion on transmission lines [128,129]. As a result of the high power and energy density of Battery Energy Storage, it is ideal for compensating for fluctuations and forecasting errors [130][131][132]. In contrast, a lack of BESS capacity may compromise reliability and safety [133].…”
Section: Energy Storage Systemmentioning
confidence: 99%
“…In ref. [33], techno-economic optimization of battery storage for grid-level energy services using curtailed energy from wind is performed. In ref.…”
Section: Literature Reviewmentioning
confidence: 99%